'Appeasement Gone Mad': The Riga Ghetto Case and the Politics of British War Crimes Trials. (July 2022) - Miner, Samuel
This article examines the British Foreign Office decision to abandon a British-run war crimes trial after the Second World War against suspected perpetrators of the Holocaust in Latvia and the efforts of a Holocaust survivors' organization to seek justice. Faced with repeated inquiries from The Association of Baltic Jews in Great Britain and their parliamentary allies, the Foreign Secretary Ernest Bevin repeated a lie told to him by his subordinates that Holocaust victims were imprecise in their testimony, making them unreliable witnesses and justifying the release of several suspected war criminals. Although very few German and Latvian perpetrators saw the inside of the courtroom, survivor advocacy countered the prevailing silence about the Holocaust in Eastern Europe during the Cold War.